Research of the mechanism of particles bonding with substrate during thermal spraying of coating. Issue 1 (November 2020) - Khrlamov, Yu O; Sokolov, V I; Krol, O S; Romanchenko, O V
Abstract: The problems of modelling of bonding of particles with a part surface during thermal spraying of coatings are considered. The formation of adhesive and cohesive strength of thermal coatings is considered from the standpoint of the theory of welding of materials in solid phase. The formation of interatomic connections between particle materials and parts is accompanied by deformation processes in contact zone, which facilitate the unloading and rupture of connections in the metal – oxygen system, loading and connections between atoms of interacting materials. The kinetics of formation of interatomic connections between materials of particle and substrate at high collision velocities is satisfactorily described by a modified semi – empirical equation that uses experimentally measured quantities: the magnitude of tensile deformation of interatomic connection, the Young's modulus, the coefficient of thermal linear expansion. Possible influence of nanotopography of substrate surface on the interaction with sprayed particles and formation of coatings with high adhesive and cohesive strength is shown.